Water Policy Entrepreneurs 2009
DOI: 10.4337/9781849803366.00017
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Integrated River Basin Management in China

Abstract: ABSTRACT. This paper examines the role of the World Wildlife Fund for Nature China as policy entrepreneur in China. It illustrates the ways in which the World Wildlife Fund for Nature is active in promoting integrated river basin management in the Yangtze River basin and how the efforts at basin level are matched with the advice of the China Council for International Cooperation on Environment and Development task force on integrated river basin management to the national government of China. This article demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Fourth, as to better understand to what extent the context in which this research was conducted might have influenced our resultsthat is, a small country marked by a dense and highly consensus-based policy network-future research needs to draw on an extended research design that includes international comparisons. After all, Te Boekhorst et al (2010) have shown that policy entrepreneurs in a centralized country such as China have a rather different role and position as compared with those in European countries. …”
Section: Discussionmentioning
confidence: 99%
“…Fourth, as to better understand to what extent the context in which this research was conducted might have influenced our resultsthat is, a small country marked by a dense and highly consensus-based policy network-future research needs to draw on an extended research design that includes international comparisons. After all, Te Boekhorst et al (2010) have shown that policy entrepreneurs in a centralized country such as China have a rather different role and position as compared with those in European countries. …”
Section: Discussionmentioning
confidence: 99%
“…Aimed at restoring ecological conditions at river basin level, it is applied to mitigate human pressures on natural ecosystems and to promote a healthy ecological environment [3][4][5]. Defined by the Global Water Partnership [1] as "the process of coordinating conservation, management and development of water, land and related resources across sectors within a given river basin in order to maximize the economic and social benefits derived from water resources in an equitable manner while preserving and/or restoring freshwater ecosystems", it is a holistic and unified approach [1].…”
Section: Introductionmentioning
confidence: 99%
“…The fact is, there are very few reported cases of public participation in the design of flood retention areas in Asia. The participatory process studied by Te Boekhorst et al () in China was organised by a nongovernmental organisation. To date, there have been no studies on the extent to which—whether or not in the framework of formal public participation processes—Asian public agencies combine flood retention measures and compensation schemes that meet the interests of farmers located in the areas that will be flooded and hence facilitate their acceptance of the project.…”
Section: Introductionmentioning
confidence: 99%